Exogenous abscisic acid and jasmonic acid restrain polyethylene glycol‐induced drought by improving the growth and antioxidative enzyme activities in pearl millet. Issue 2 (10th November 2020) - Awan, Samrah A.; Khan, Imran; Rizwan, Muhammad; Zhang, Xinquan; Brestic, Marian; Khan, Aaqil; El‐Sheikh, Mohamed A.; Alyemeni, Mohammed N.; Ali, Shafaqat; Huang, Linkai
Abstract: Drought stress is one of the most immense and permanent constraints in agriculture, which leads to a massive loss of crop productivity. However, little is known about the mitigation role of exogenously applied abscisic acid (ABA) and jasmonic acid (JA) in pearl millet ( Pennisetum glaucum L.) under PEG‐induced drought stress. Therefore, the current study investigated the putative role of exogenous ABA and JA in improving drought stress tolerance in pearl millet. Thirteen‐day‐old seedlings were exposed to six different treatments as follow; control (ck), PEG‐600 (20%), JA (100 μM), ABA (100 μM), PEG+JA, and PEG+ABA, and data were collected at 7 and 14 days after treatment (DAT). Results showed that PEG decreased plant growth while the oxidative damage increased due to over production of H2 O2 and MDA content as a result of decreased activities of the antioxidative enzymes including APX, CAT, and SOD in the leaves. However, exogenous ABA and JA positively enhanced the growth profile of seedlings by improving chlorophyll and relative water content under PEG treatment. A significant improvement was observed in the plant defense system resulting from increased activities of antioxidative enzymes due to exogenous ABA and JA under PEG. Overall, the performance of JA was found better than ABA under PEG‐induced drought stress, and future investigations are needed to explore the potential effects of these phytohormones on the long‐term crop management and productivity under drought stress.